2021
DOI: 10.3389/fcvm.2021.752675
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Out-of-Hour Admission and Short- and Long-Term Mortality in Acute Myocardial Infarction: A Systematic Review and Meta-Analysis

Abstract: Objectives: Out-of-hour admission (on weekends, holidays, and weekday nights) has been associated with higher mortality in patients with acute myocardial infarction (AMI). We conducted a meta-analysis to verify the association between out-of-hour admission and mortality (both short- and long-term) in AMI patients.Design: This Systematic review and meta-analysis of cohort studies.Data Sources: PubMed and EMBASE were searched from inception to 27 May 2021.Eligibility Criteria for Selected Studies: Studies of any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…It is comparatively easy to explain this finding by the significantly greater clinical burden and co-morbidities of those patients, which had a direct impact on the increased death risk. Aspects connected with the influence of the time of MI patients’ admission to hospital on their prognosis as well as the causes of these differences have been raised many times in the literature [ 49 ]. Conclusions from these studies remain unclear and mutually contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…It is comparatively easy to explain this finding by the significantly greater clinical burden and co-morbidities of those patients, which had a direct impact on the increased death risk. Aspects connected with the influence of the time of MI patients’ admission to hospital on their prognosis as well as the causes of these differences have been raised many times in the literature [ 49 ]. Conclusions from these studies remain unclear and mutually contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the miR-30 family are abundantly expressed in cardiac tissue and are extensively involved in the pathophysiology of a variety of heart diseases (27)(28)(29). The miR-30 family also plays a protective role in diseases, such as myocardial hypertrophy, myocardial infarction, heart failure, and ischaemia-reperfusion injury (30)(31)(32)(33). Further, a previous study showed that miR-30e-3p expression was significantly reduced after coronary microembolization (CME) (34).…”
Section: Discussionmentioning
confidence: 99%
“…We performed subgroup analyses based on follow-up duration, diabetic status, type of AMI, time to PCI, geographical region, adequate adjustment, study quality, and glucose level assessment. Newcastle–Ottawa Scale (NOS) was used to assess the quality of included studies in this meta-analysis ( 15 ). Three domains (cohort selection, comparability, and outcome) were independently assessed by three investigators (J.-H. W., H.W., and X.-C. D.).…”
Section: Methodsmentioning
confidence: 99%